Kesadaran Masyarakat terhadap Larangan Melawan Arah dan Faktor Penyebab Pengendara Lawan Arah: Studi Hukum pada Pengendara di Depan Universitas Pancasila - Farel Aliifa Rasya; Yatna Firdaus Hidayat; Rachmawati Syarifudin; Bima Sayyid Haidar; Sandi Ar Rayyansyah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Traffic violations in the form of driving against the designated direction are a common phenomenon on various urban roads, including the area in front of the Faculty of Law, Pancasila University, Lenteng Agung, South Jakarta. This study aims to identify the level of public awareness regarding the prohibition of driving against traffic and to analyze the factors that encourage motorists to commit such violations. The research employed an empirical method with a field-based approach. Primary data were obtained through interviews and direct observations of motorists identified as driving against traffic at the research location, while secondary data were collected from traffic regulations, particularly Law Number 22 of 2009 concerning Road Traffic and Transportation, as well as relevant academic literature. The findings indicate that public legal awareness regarding the prohibition of driving against traffic remains relatively low, even though most respondents are aware of the regulation. The main factors contributing to these violations include the desire to avoid traffic congestion, save travel time, inconsistent law enforcement, and inadequate road infrastructure design. Ironically, such violations are often committed by educated individuals within the university environment, indicating that a higher level of education does not necessarily correlate with legal compliance. This study recommends strengthening periodic law enforcement, increasing traffic awareness education among the academic community, and improving road infrastructure as comprehensive measures to reduce the incidence of traffic violations.